Minimally processed yellow melon subjected to different natural polymers (Research, Society and Development, 2021)
The population's busy lifestyle makes consumers look for alternatives that optimize time at mealtimes. Within this context, there are minimally processed fruits, where the melon stands out because its production is intended for fresh consumption. The use of natural polymers has been used as one of the alternatives to increase the shelf life of minimally processed fruits and vegetables. Thus, the objective of this research is to find the coating formulation that provides a longer post-cut conservation period. The fruits were minimally processed into cubes and subjected to natural polymers by immersion, five treatments being quantified and evaluated every 2 days for 10 days of storage (0, 2, 4, 6, 8 and 10 days) for physical characteristics, physicochemical and bioactive compounds. The developed natural polymers, associated with refrigeration, formed a film on the surface of the minimally processed melons, providing less weight loss to the fruits, ensuring stability in terms of pH and titratable acidity. They also presented satisfactory levels of ascorbic acid and flavonoids, which are potential sources of natural bioactive compounds for the human diet, with emphasis on the coating with yam starch (Trat.4) being the most effective in maintaining the levels of ascorbic acid, carotenoids and fruit quality.